Evaluating public expectation on physical and functional factors of community center design in Kuala Lumpur, Malaysia - Jafari, Nastaran (2015)
Community center as a public space must be seen and treated as a crucial part of the planning process for urban development. The Malaysian Government is consistently to improve the quality of life with Malaysian’s aspiration toward becoming a developed nation. The main objective of this thesis is to identify significant criteria for formulating a design framework for responsive community centers based on community expectation in the Malaysia. To achieve this objective, four community centers in four regions of Kuala Lumpur were used as the case studies to show the participants expectation and evaluation toward using the community center in terms of physical and functional factors. Quantitative research was conducted in this research and data was collected through questionnaire survey and analyzed by using SPSS. The result of the questionnaire presented that, participants did not agree with the current situation of Malaysian Community centers, especially in terms of functional factor. The research also exposed and identified that access by public transport and condition of ventilation and lighting were the most important features in terms of physical factor. Moreover, having open space was the most important features in terms of functional factor which should be more considered and used in the future structure of Malaysian community centers. So, this study will contribute to City Hall architect, planners and urban designers who are in charge of the community center design to reconstruct and redesign better community center in Kuala Lumpur, Malaysia.